2003
DOI: 10.1046/j.1365-2133.2003.05091.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial photodynamic therapy: assessment of genotoxic effects on keratinocytes in vitro

Abstract: APDT sufficient to reduce microbes by seven log cycles showed no detectable genotoxic effects on keratinocytes. APDT applied in vivo may represent a useful low-risk alternative to conventional antimicrobial treatment in dermatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 13 publications
0
49
0
3
Order By: Relevance
“…The potential for topical application to affected areas in mucocutaneous candidiasis and application of light only to affected areas makes these infections particularly amenable to approach by PDT. Zeina et al have demonstrated that PDT with methylene blue under conditions that lead to effective killing of typical skin microbes, including C. albicans cause neither cytotoxicity (24) nor DNA damage to keratinocytes in vitro (23). These observations lend support to the notion that selectivity for the microbe may be possible for mucocutaneous candidiasis, but gathering in vivo data will also be important.…”
Section: Discussionmentioning
confidence: 48%
“…The potential for topical application to affected areas in mucocutaneous candidiasis and application of light only to affected areas makes these infections particularly amenable to approach by PDT. Zeina et al have demonstrated that PDT with methylene blue under conditions that lead to effective killing of typical skin microbes, including C. albicans cause neither cytotoxicity (24) nor DNA damage to keratinocytes in vitro (23). These observations lend support to the notion that selectivity for the microbe may be possible for mucocutaneous candidiasis, but gathering in vivo data will also be important.…”
Section: Discussionmentioning
confidence: 48%
“…According to some authors, it seems to be part of the normal skin flora, and therefore it would be responsible for infectious and inflammatory processes in very few cases [65] . Conversely, other authors have dealt with PDT for the treatment of S. epidermidis as an infection rather than as a mere colonizer [65] . Many studies showed the efficacy of PDT against this bacterial component, with different types of methods and photosensitizers.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…It is well known that PDT shows antibacterial effects [44,45] and that the role of a bacterial component could be considered in HS pathogenesis. PDT likely benefits HS because it disrupts the biofilm that is commonly created by Staphylococcus epidermidis and Staphylococcus aureus in HS lesions [65] . The effect of S. epidermidis on the human skin is controversial.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…Kömerik et al 15 observed complete inactivation of Porphyromonas gingivalis in the maxillary molar region of rats after PDT, with no adverse effects on the periodontal structures after 3 days and significant reductions in bone loss after 90 days. Moreover, Zeina et al 16 detected no genotoxicity (immediate and delayed effects) on skin cells after a PDT protocol that was effective for killing microbial species. These authors concluded that there is a wide safety margin for PDT between microbial elimination and damage to host cells.…”
mentioning
confidence: 99%